"They Will Find Another Way to Hurt You": Emerging Adults' Perceptions of Coping With Cyberbullying. Issue 1 (February 2021) - Alipan, Alexandra; Skues, Jason L.; Theiler, Stephen
To date, there is a limited amount of research exploring how emerging adults cope with cyberbullying despite being prolific users of technology. The aim of this qualitative study was to explore emerging adults' views, opinions, and perceptions of how individuals within this developmental period cope with being targeted by cyberbullying behaviors. Six focus groups were conducted with 39 participants (64% female) between 18 and 25 years of age in Melbourne, Australia. Thematic analysis of the data identified several coping strategies that can be employed in response to cyberbullying, which were categorized as problem-focused coping, emotion-focused coping, or cyber-specific technological solutions. In addition to these ways of coping, two notable findings provide insight into the complex and dynamic pattern of perceptions of control and coping style selection and the perceived effectiveness of such coping strategies. This study has implications for targets of cyberbullying, research, and practice.